Ebola Outbreaks in the Democratic Republic of Congo (DRC), 2017-2019 - Phi-Yen Nguyen (University of New South Wales, 2019)
Three genetically-distinct Ebola virus disease (EVD) outbreaks have occurred in the Democratic Republic of Congo (DRC) since May 2017: the 2017 Bas-Uélé outbreak, the 2018 Équateur outbreak and the 2018-19 North Kivu outbreak. The latest outbreak, currently ongoing, is the second largest EVD outbreak in history, with 1,617 confirmed cases as of 12 May 2019. New clusters continue to emerge despite unprecedented advances in vaccinations, diagnostics and therapeutics. In this Watching Brief, we review key features of all three outbreaks, evaluate vaccination strategy used and critically examine factors that contribute to the North Kivu outbreak's persistence. The North Kivu outbreak is characterised by multiple issues that hamper disease control measures, including socio-political barriers (armed conflicts and community resistance) and operational deficiencies (ineffective contact tracing and infection control in health facilities). Evidence also suggests possible sexual transmission of EVD by persistently-infected survivors.